Collusion-resistant fingerprinting for multimedia. - Min Wu
Digital fingerprinting is a technology for enforcing digital rights policies whereby unique labels, known as digital fingerprints, are inserted into content prior to distribution. For multimedia content, fingerprints can be embedded using conventional watermarking techniques that are typically concerned with robustness against a variety of attacks mounted by an individual. These attacks, known as multiuser collusion attacks, provide a cost-effective method for attenuating each of the colluder's fingerprints and poses a real threat to protecting media data and enforcing usage policies. In this article, we review some major design methodologies for collusion-resistant fingerprinting of multimedia and highlight common and unique issues of different fingerprinting techniques. It also provides detailed discussions on the two major classes of fingerprinting strategies, namely, orthogonal fingerprinting and correlated fingerprinting.
Keywords: Colluder identification; Colluder tracing; Collusion-resistant fingerprinting; Correlated fingerprinting; Digital fingerprinting; Digital rights policies; Multimedia content; Multiuser collusion attacks; Orthogonal fingerprinting; Watermarking techniques